Application of the Tafsir Tarbawi Concept in Ethical and Moral Education - Ahmad Rival Anshori; Ahmad Mirza (Penerbit Hellow Pustaka, 2025)
Ethical and moral education is one of the fundamental elements in forming individuals with good character and virtuous values in social life. In the Islamic context, integrating religious values is an important basis in building a generation with noble character. One relevant approach to realizing this goal is through the application of the concept of tarbawi interpretation. Tarbawi interpretation is a method of interpretation of the Qur'an that focuses on educational aspects, both individually and socially, to develop noble moral and ethical values. This concept offers a practical guide to internalizing the teachings of the Qur'an in the context of applicable ethical and moral education. This paper aims to explore the application of tarbawi interpretation as an educational approach that can strengthen the character formation of students. By integrating the teachings of the Koran which are interpreted tarbawi, educators can present learning methods that are not only theoretical, but also emphasize the application of these values in everyday life. The discussion begins with an explanation of the concept of tarbawi interpretation, its basic principles, and its relevance in education. Furthermore, this paper evaluates the extent to which the concept of tarbawi interpretation can be applied in ethical and moral education curricula at various levels of education, both formal and non-formal. The results of the study show that the application of tarbawi interpretation is able to provide a deep understanding of the importance of universal values taught in Islam, such as honesty, responsibility, justice and tolerance. With this approach, students are not only invited to understand religious teachings textually, but are also directed to practice them in various aspects of life. Apart from that, tarbawi interpretation also allows educators to design learning materials that suit the needs of the times without eliminating the essence of Islamic teachings. Thus, this paper concludes that the concept of tarbawi interpretation contributes significantly to building a holistic and sustainable ethical and moral education system. Further research is needed to develop more effective implementation methods and models so that the values of the Qur'an can be optimally integrated in every aspect of educational life.